Students’ Motivation In Learning English By Using Blended Learning SMK HKBP Pematangsiantar - Rina Octavia Simarmata; Febrika Dwi Lestari (Journal on Education, 2023)
This research aims to determine the components of student motivation in learning English with blended learning in class XI students at SMK HKBP Pematangsiantar. Therefore, the formulation of the problem in this study is "The difficulties of students in learning English, lack of vocabulary and lack of time in class XI students of SMK HKBP Pematangsiantar in understanding Blended Learning? And what is the cause of this error?” To find out the answer to the problem in this study, researchers used related theories, namely Diasti, K. S. (2020), Sari I. et all, (2018), The methodology used in this research is qualitative research and the questionnaire is a data collection technique. This is used to identify and describe the level of difficulty of students in learning students' English vocabulary. The data selected in this study were all students of class XI SMK Pariwisata HKBP Pematangsiantar, totaling 29 students. After the data was collected, the researcher found that there were four types of errors in writing students' descriptive texts, namely negligence, addition, misformation and misordering and there were four types of causes, namely difficulty understanding English, inappropriate timing (running out of chasing time assigned by the teacher) Thus it can be concluded that class XI students of SMK Pariwisata HKBP Pematangsiantar do not know how to increase motivation to learn English by using blended learning. Researchers suggest that teachers play a role in motivating students to be effective when teaching in class.